Reflections on the Woodhouse Legacy for the 21st Century - St John, Susan (Victoria University of Wellington Law Review, 2020)
This lecture commemorates the life of one of our most distinguished judges and citizens, Sir Owen Woodhouse. His compassion, generosity of spirit and social conscience were reflected in his work as President of the Court of Appeal, President of the Law Commission and Chairman of the Royal Commission on Compensation for Injury that recommended a no-fault accident compensation scheme and laid the foundations for the Accident Compensation Corporation (ACC) scheme. He made an immense contribution to New Zealand's law and society.